Praktik Tata Tertib Berlalu Lintas: Upaya Edukasi Pemahaman dan Penerapan Nilai-Nilai Pancasila pada Peserta Didik Sekolah Dasar - Aulina, Khanifa Kinanthi; Lestari, Endriyani; Saputra, Errix Dwi; Malik, Abdul (Universitas Negeri Semarang, 2025)
The aim of this community service is to provide education on understanding and implementing Pancasila values ​​and traffic regulations to elementary school students. The fading of Pancasila values ​​can be seen from the many traffic violations involving the younger generation. This behavior is considered to deviate from the values ​​contained in Pancasila, especially the second principle of Pancasila. Therefore, it is necessary to strengthen Pancasila values ​​in the younger generation, especially elementary school students. The approach used is Participatory Action Research (PAR) with the Participatory Rural Appraisal (PRA) technique. The community service team divided the activities into three sessions. The first session includes education on understanding and implementing Pancasila values. The second session includes an introduction to traffic regulations and traffic signs as an example of implementing Pancasila values. The third session is practicing traffic regulations as an implementation of the second principle of Pancasila.